Bygder og barakker: Arbejdspladsen som konfliktzone i dansk grønlandslitteratur - Dybdal, Emilie; Grønlund, Anders (Passage - Tidsskrift for litteratur og kritik, 2020)
This article examines how work plays a major role in Danish literature about Greenland – often with the workplace as a zone of conflict. At first, a short history of Danish litera- ture about Greenland is presented followed by an analysis of Jørgen Liljensøe’s novel Barakkerne (1977). Lastly, we will discuss the latest Danish literature about Greenland by Kim Leine and Iben Mondrup. Our approach will primarily be informed by theories on space and place but also involve postcolonialism.